Effects of high pressure processing on gelation properties and molecular forces of myosin containing deacetylated konjac glucomannan. (1st September 2019) - Li, Zhiyu; Wang, Jianyi; Zheng, Baodong; Guo, Zebin
Highlights: Deacetylated konjac glucomannan induced partly unfolding of myosin. Deacetylated konjac glucomannan protected myosin from denaturation and aggregation. Suitable pressure level could improve thermal gelling ability and gelation properties. The synergism of deacetylated konjac glucomannan and 300 MPa contributed to fine gel. Abstract: This study investigated the gelation properties of composite gels prepared with golden threadfin bream myosin and 2% (w/v) deacetylated konjac glucomannan under different high pressure processing (HPP). Deacetylated konjac glucomannan increased the immobilized water and increased the gel strength of myosin gel, which were further increased under moderate pressure level (0.1–300 MPa) but decreased under strong pressure level (400–500 MPa). HPP induced unfolding of myosin and the partial transformation of α-helix into other structures (β-sheet, β-turn and random coil). Dynamic rheological tests indicated that storage modulus of the pressurised myosin was increased to maximum under 100 MPa. Scanning electron microscopy images revealed that HPP at 300 MPa produced a compact networked microstructure. Moreover, the molecular forces analysis proved that the increase in immobilized water of pressurised gels was mainly attributed to enhanced hydrogen bonds and electrostatic interactions, while the HPP-induced hydrophobic interactions were dominating mechanism to improve gel strength.